Control of vehicular emission using innovative energy solutions comprising of hydrogen for transportation sector in Pakistan: A case study of Lahore City. (11th June 2020) - Shirwani, Rummana; Gulzar, Saima; Asim, Muhammad; Umair, Muhammad; Al-Rashid, Muhammad Ahmad
Abstract: Energy, either from non-renewable or renewable sources, is of paramount importance as the progress of a country is gauged on economic development. However, with the use of non-renewable energy resources, the environmental degradation is exacerbating with every passing day in developing countries including Pakistan. On the contrary, the developed countries are resorting to sustainable and renewable energy resources to achieve sustainable development goals. The primary consumer of the non-renewable energy sources is transportation sector in Pakistan, with the total consumption amounting to almost two-third of the total utilization. Keeping in view the existing energy expenditures and its share in environmental pollution by transportation sector, Lahore Metropolitan area has been selected for this research paper. This research analyzed the environmental data collected from multiple road junctions of Lahore City. In light of the existing data, the research exhibited improvements in overall environmental quality by comparing the existing and proposed energy solutions comprising of Hydrogen in transportation sector. The comparison carried out by utilizing International and National Environmental quality standards. Additionally, research also addresses the energy savings with the transition from non-renewable energy sources to renewable and innovative energy solutions. Highlights: Environmental degradation is exacerbating with use of non-renewable energy resources. Primary consumer of non-renewable energy sources is transportation sector in Pakistan. Comparison of the existing and proposed energy solutions. Comprising of Hydrogen fuel cell in transportation sector. Hydrogen fuel cell technologies for the transportation sector for safe and clean future.